English language in Brunei: Use, policy, and status in education – A review - Claire Goode (Universitas Katolik Indonesia Atma Jaya, 2020)
This paper explores the literature on the status of the English language in Negara Brunei Darussalam, particularly in education. The review encompasses a total of 103 sources, including 44 journal articles, 27 book chapters, 15 books, and 17 other items (institution/organisation websites and reports, government documents, newspaper articles, and conference presentations), published between 1985 and 2020, with at least 70 sources published in the last decade. The author summarises findings from research in key areas in the Bruneian context including bilingual education, linguistic diversity, the status of English, educational policies, educational divides, and challenges to the student experience, particularly in higher education in the bilingual setting. The author found that: i) while there are concerns over the impact of English on the Malay language and on indigenous languages in the Sultanate, and apprehension around an educational divide, the majority of attitudes appear to be very positive about the use of English in Brunei, including in education; ii) the bilingual education policy has evolved over time, and now places an emphasis on English as a key competency for the 21st century; iii) the student experience in the bilingual context is a particularly under-researched area. Staff working in tertiary education can always benefit from further insights into different aspects of learning, teaching, and content delivery, which may be applicable in many settings. The paper concludes with recommendations for further research in Brunei.